Human Papilloma Virus: Biomolecular Aspect - Patiyus Agustiansyah; Rizal Sanif; Siti Nurmaini; Irfannuddin; Legiran (HM Publisher, 2021)
HPV is a sexually transmitted virus, and high-risk HPV DNA was found in 99.7%of cervical cancer specimens. Within 12 to 24 months of exposure to the virus,90% of HPV infections disappear or become inactive. However, infection with high-risk strains of HPV persist which then increases the risk of progression to cervicalcancer. The detection of precancerous lesions consists of various methods,including pap smear (conventional or liquid-base cytology / LBC), visualinspection of acetic acid (IVA), visual inspection of lugoliodine (VILI), and HPV DNAtest (genotyping / hybrid capture).